2020
DOI: 10.3390/ijms21124441
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Cells and Their Contribution to T-Cell-Based Immunotherapy

Abstract: In recent years, immunotherapy has become the most promising therapy for a variety of cancer types. The development of immune checkpoint blockade (ICB) therapies, the adoptive transfer of tumor-specific T cells (adoptive cell therapy (ACT)) or the generation of T cells engineered with chimeric antigen receptors (CAR) have been successfully applied to elicit durable immunological responses in cancer patients. However, not all the patients respond to these therapies, leaving a consistent gap of therapeutic impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 187 publications
(228 reference statements)
0
20
0
Order By: Relevance
“…During tumorigenesis, myeloid cells (including myeloid-derived suppressor cells (MDSCs), macrophages, neutrophils) typically accumulate in the early stage of tumor outgrowth to suppress the T cell response and sustain an immunosuppressive environment. 169 Dendritic cells (DCs) deliver tumor antigens to T cells and natural killer (NK) cells that exert antitumor cytotoxic effects. 170 However, antitumor immune reactions often become suppressed during tumor development; TGFβ can exhibit pivotal immunosuppressive effects on the intrinsic antitumor potential of DCs and NK cells in the TME (Fig.…”
Section: Functions Of Tgfβ In the Tmementioning
confidence: 99%
“…During tumorigenesis, myeloid cells (including myeloid-derived suppressor cells (MDSCs), macrophages, neutrophils) typically accumulate in the early stage of tumor outgrowth to suppress the T cell response and sustain an immunosuppressive environment. 169 Dendritic cells (DCs) deliver tumor antigens to T cells and natural killer (NK) cells that exert antitumor cytotoxic effects. 170 However, antitumor immune reactions often become suppressed during tumor development; TGFβ can exhibit pivotal immunosuppressive effects on the intrinsic antitumor potential of DCs and NK cells in the TME (Fig.…”
Section: Functions Of Tgfβ In the Tmementioning
confidence: 99%
“…TAMs exist widely in the anoxic region of TME, and most of them are M2 polarized, resulting in immunosuppressive phenotype and inhibition of T cellmediated adaptive immunity. A series of studies have shown that TAMs affect the therapeutic effect of anti-pd-L1 and anti-CTLA-4 drugs to a great extent, and the curative effect has been observed when traditional immunotherapy were combined with macrophage targeting strategy (Ginefra et al, 2020), but its specific mechanism needs to be further explored.…”
Section: The Regulatory Mechanism Of the Tumor Immune System The Immunomodulatory Mechanism Of Macrophage Cellmentioning
confidence: 99%
“…In previous studies, pDC is mainly by producing I-IFN to participate in antiviral immunity or other dendritic cell activation; In contrast, cDC can further differentiate through the expression of surface immune receptors, or through crosspresent antigens and other ways to activate anti-tumor specific immune effects (Chan and Housseau, 2008). Thus, the DC can be used to stimulate immature T lymphocytes, which forms a heterogeneous group of specialized antigens presenting cell (APC), and its function is integrated into innate and adaptive immune responses (Ginefra et al, 2020).…”
Section: The Immunomodulatory Mechanism Of Dendritic Cellsmentioning
confidence: 99%
See 2 more Smart Citations